Acute exercise and caffeine improve insulin-induced hypoglycemia in normal and malnourished rats - Babata, Lucas Kazunori Rubira; Malta, Ananda; Godoi, Vilma Aparecida Ferreira de; Pedrosa, Maria Montserrat Diaz (Acta Scientiarum. Biological Sciences, 2015)
In food restriction, hypoglycemic episodes can be more severe and persistent. This study assessed the influence of acute exercise and caffeine on the insulin-induced hypoglycemia in freely-fed or malnourished (50% food restriction) young rats. At the age of 60 days, rats under overnight fasting received an insulin injection to cause an episode of hypoglycemia. In some animals, hypoglycemia was preceded by an acute session of exercise, in others, caffeine was orally given 15 minutes after insulin injection; or exercise and caffeine were combined. Blood samples were collected at regular intervals for five hours after insulin injection. A beneficial effect of both exercise or caffeine on the hypoglycemic episode in the malnourished rats was found. In the control rats, the association of exercise+caffeine was more beneficial than either intervention alone. It is discussed that exercise and caffeine, alone or combined, can be used as exogenous anti-hypoglycemic resources, but considering the nutritional status of the subject.